Distribution and frequency of genetic mutations in three insecticide targets in field populations of Culex tritaeniorhynchus in Mianyang City, Sichuan Province, China - Xie, Hongwei; Tang, Meilin; Sun, Hongying; Huang, Zhengzheng; Dong, Mengmeng; Wen, Xianying (Frontiers in Cellular and Infection Microbiology, 2025)
Japanese encephalitis (JE) is an important mosquito borne infectious disease which is mainly transmitted by Culex tritaeniorhynchus Giles (1901) in China. At present, vector control remains an important means to prevent and control vector-borne diseases including JE. The development of insecticide resistance has seriously threatened the effectiveness of insecticide-based vector control programmes. Therefore, understanding insecticide resistance in the target pest is essential to inform evidence-based vector control. In Mianyang City of Sichuan Province of China, Cx. tritaeniorhynchus is the dominant mosquito species, and JE has been documented in this city. Unfortunately, there is little information on the status and underlying mechanisms of insecticide resistance in field populations of Cx. tritaeniorhynchus, the main JE vector in this region. In the study, a total of 314 adults of Cx. tritaeniorhynchus, collected from 6 sites across Mianyang City, were inspected for resistance-conferring mutations in three genes encoding voltage-gated sodium channel (VGSC), Gamma-aminobutyric acid (GABA) receptor Rdl subunit (Rdl), and acetylcholinesterase (AChE) by DNA Sanger sequencing. The results showed that the classical L1014F mutation in VGSC was distributed in all the 6 populations at varying frequencies from 16.98% to 27.78%, and the frequency of F455W mutation in AChE was extremely high (97.06%-100%). Notably, the conserved mutations A296S and V327I previously reported in the Rdl of some other species of mosquitoes were discovered in Cx. tritaeniorhynchus for the first time. The frequency of the resistant Rdl 296S allele was 62.04% to 94.00%, while the V327I mutation was present at a much lower frequency ranging from 0.93% to 1.8%. Overall, the prevalent co-existence of resistance-conferring mutations in multiple insecticide target proteins in Cx. tritaeniorhynchus populations in Mianyang City indicates a worrying status of insecticide resistance, and suggests that it is highly required to monitor the phenotypic resistance of Cx. tritaeniorhynchus on a regular basis.